2015
DOI: 10.3329/icpj.v4i2.21482
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoepidemiology of ascites and associated complications in hospitalized patients: descriptive observational study

Abstract: Ascites is the pathological accumulation of free fluid in peritoneal cavity. The aim of the present study was to observe the prevalence, clinical management and the assessment of complications associated with ascites in hospitalized patients. A Descriptive Observational Study was conducted at two tertiary care hospitals of Lahore. The data was collected on a data collection form containing questions regarding basic patient information, presenting symptoms, clinical management and associated complications. Verb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
2
1
2
Order By: Relevance
“…Liver cirrhosis was found to be the main cause of ascites in this study similar to other studies done elsewhere [10, 14–18]; however, the proportion of ascites caused by liver cirrhosis was lower as compared to the studies conducted in USA, Qatar, and Ethiopia [10, 15, 17]. This could be because of the higher tuberculosis and hepatosplenic schistosomiasis in the current study, where such infections are epidemic in the study setting.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Liver cirrhosis was found to be the main cause of ascites in this study similar to other studies done elsewhere [10, 14–18]; however, the proportion of ascites caused by liver cirrhosis was lower as compared to the studies conducted in USA, Qatar, and Ethiopia [10, 15, 17]. This could be because of the higher tuberculosis and hepatosplenic schistosomiasis in the current study, where such infections are epidemic in the study setting.…”
Section: Discussionsupporting
confidence: 85%
“…Heart failure, tuberculosis, and hepatosplenic schistosomiasis were relatively more common in this study in contrast to studies done in the USA, Qatar, and Pakistan [10, 14, 15]. However, tuberculosis incidence (11.5%) in this study was lower in contrast to the study done in Nigeria (22%) but was comparable to a previous Ethiopian study (9%).…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…This is comparable with other studies conducted in Africa and in the Western world. 1,2,5,[11][12] For instance, these findings are similar to a study conducted in Nigeria which showed similar aetiologies of ascites. 11 However, patients in the Nigeria study had a lower prevalence of liver cirrhosis (44%), and high percentages of tuberculous peritonitis (23%) and malignant ascites (22%).…”
Section: Discussionsupporting
confidence: 82%
“…Examples of mixed ascites include liver cirrhosis plus peritoneal carcinomatosis, peritoneal tuberculosis, heart failure or renal failure and liver cirrhosis plus heart failure and diabetic nephropathy. In the latter case, cirrhosis complicates non-alcoholic steatohepatitis 11 .…”
Section: Introductionmentioning
confidence: 99%